Near-Infrared Saturable Absorption of Defective Bulk-Structured WTe2 for Femtosecond Laser Mode-Locking - Koo, Joonhoi; Jhon, Young In; Park, June; Lee, Junsu; Jhon, Young Min; Lee, Ju Han (John Wiley & Sons Ltd., 2016)
Mono- and few-layer transition metal dichalcogenides (TMDCs) have been widely used as saturable absorbers for ultrashort laser pulse generation, but their preparation is complicated and requires much expertise. The possible use of bulk-structured TMDCs as saturable absorbers is therefore a very intriguing and technically important issue in laser technology. Here, for the first time, it is demonstrated that defective, bulk-structured WTe2 microflakes can serve as a base saturable absorption material for fast mode-lockers that can produce femtosecond pulses from fiber laser cavities. They have a modulation depth of 2.85%, from which stable laser pulses with a duration of 770 fs are readily obtained at a repetition rate of 13.98 MHz and a wavelength of 1556.2 nm, which is comparable to the performance achieved using mono-and few-layer TMDCs. Density functional theory calculations show that the oxidative and defective surfaces of WTe2 microflakes do not degrade their saturable absorption performance in the near-infrared range, allowing for a broad range of operative bandwidth. This study suggests that saturable absorption is an intrinsic property of TMDCs without relying on their structural dimensionality, providing a new direction for the development of TMDC-based saturable absorbers.